Gluttony and gratitude Milton's philosophy of eating - Stelzer, Emily E. (Medieval and Renaissance literary studies., 2017)
"Explores the philosophical significance of gluttony in Paradise Lost, arguing that a complex understanding of gluttony and of ideal, grateful, and gracious eating informs the content of Milton's writing"--